2001
DOI: 10.3109/15419060109080759
|View full text |Cite
|
Sign up to set email alerts
|

Cx36 and the Function of Endocrine Pancreas

Abstract: The secretory, duct, connective and vascular cells of pancreas are connected by gap junctions, made of different connexins. The insulin-producing beta-cells, which form the bulk of endocrine pancreatic islets, express predominantly Cx36. To assess the function of this connexin, we have first studied its expression in rats, during sequential changes of pancreatic function which were induced by the implantation of a secreting insulinoma. We observed that changes in beta-cell function were paralleled by changes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 13 publications
(9 reference statements)
1
13
1
Order By: Relevance
“…Furthermore, in agreement with this study, reelin (involved in cell-cell aggregation) transcript levels in MIN-6(H) were much lower than in MIN-6(L). A major component of cell-cell communication in pancreatic islets involves the connexins, particularly C!43 (Meda et al 1991) and C!36 (Calabrese et al 2001). These transcripts were, however, flagged absent in our studies.…”
Section: Adhesion/proliferationcontrasting
confidence: 47%
“…Furthermore, in agreement with this study, reelin (involved in cell-cell aggregation) transcript levels in MIN-6(H) were much lower than in MIN-6(L). A major component of cell-cell communication in pancreatic islets involves the connexins, particularly C!43 (Meda et al 1991) and C!36 (Calabrese et al 2001). These transcripts were, however, flagged absent in our studies.…”
Section: Adhesion/proliferationcontrasting
confidence: 47%
“…These results suggest that Cx43 is an essential early connexin gene needed for the initial establishment of GJIC, which is subsequently needed for the expression of the Cx36 gene normally observed in differentiated pancreatic islet tissue. [56][57][58][59] Connexin 26 (Cx26)-which was reported to be expressed in islets of Langerhans 60 -was not detected in H6c7 cells by Western Blot analysis in our previous study. 61 Cx26 protein or gene expression was not upregulated by cyclic AMP.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have implicated Cx-mediated cell-to-cell coupling in β-cell function (Bosco et al, 1995;Calabrese et al, 2001;Cao et al, 1997;Vozzi et al, 1995) and have suggested that adequate levels of specific Cx isoforms is required for the control of insulin secretion of permanent cell lines (Calabrese et al, 2001;Cao et al, 1997;Vozzi et al, 1995). As yet, however, it has not proved feasible to test this hypothesis directly in normal pancreatic β-cells, mostly because these highly differentiated cells proliferate poorly (Nielsen et al, 1989) and hence are not amenable to the stable expression of exogenous cDNAs by standard transfection procedures.…”
Section: Discussionmentioning
confidence: 99%
“…We have found that pseudo-islets made by cells transduced with either GFP-or connexin43-expressing lentivirus released insulin in response to various several lines of evidence suggest that Cx-mediated communication between β-cells is required for control of insulin secretion. In rats, sequential changes of pancreatic function were found to parallel changes in Cx36 expression (Calabrese et al, 2001). Expression of Cx32 in β-cells of transgenic mice reduced insulin secretion in response to physiological concentrations of glucose, indicating that the in vivo expression of a Cx, which is exogenous to pancreatic islets, perturbed β-cell functioning, in spite of the persistence of the native Cx36 and increased cell-tocell coupling .…”
mentioning
confidence: 99%